Barriers and opportunities for prolonging working life across different occupational groups: the SeniorWorkingLife study. (29th August 2019) - Andersen, Lars L; Jensen, Per H; Sundstrup, Emil
Abstract: Background: Increasing retirement age is a pivotal issue in labour market reforms. This study analyses factors conditioning retirement intentions. Methods: In SeniorWorkingLife, 11 444 employed workers ≥50 years replied to questions in random order about expected reasons for leaving and potential reasons for staying longer at the labour market. Respondents were stratified based on the Danish version of International Standard Classification of Occupations (ISCO). Representative estimates were produced using the SurveyFreq and SurveyLogistic procedures of SAS combined with model-assisted weights based on national registers. Results: For ISCO groups 1–4 (seated work) main expected reasons for retiring were freedom to choose and desire for more leisure time, but many would consider staying longer if there were better possibilities for additional senior days, longer vacations and flexible working hours. For ISCO groups 5–9 (physical work), poor physical health and not being capable of doing the job were common expected reasons for retiring, but many would consider staying longer if the work were less physically demanding and there were more senior days. Possibility for pension was a general expected reason for retiring. Expected reasons differed to a less extent between genders than between ISCO groups, e.g. economic factors were more important for men and high work demands more important for women. Conclusion: Different barriers and opportunities for prolonging working life exist across different occupational groups of the labour market—with most consistent differences between those with seated and physical work. Targeting these specifically seems opportune for policy makers and future interventions.